An Integration of Short-Term Planning with Mineral Processing Simulation - F D Durao; Muge F. H; Rogado J. Q (The Australasian Institute of Mining and Metallurgy, 1995)
In the scope of the project named CAPUME II (EEC BRITE/EURAM contract - project MA2M-CT90,-0042(SMA)) for the development of an integrated mine planning system for underground mines, two of the main tasks were the development of a short-term mining planning procedure (module) and a numerical simulator of the mineral processing plant of Pirites Alentejanas - PA. The short-term mining planning module defines the mining sequences by solving a constrained minimisation problem. The ore grade variability is the objective function subject to the geometrical constraints of the mining method and to the maximum of `internal blending'. The optimisation problem is solved by applying a dynamic programming algorithm. The plant simulator is an essential tool of the planning system allowing the preview of metal grades/recoveries of copper, lead and zinc of concentrates streams, given the corresponding metal assays of the run-of-mine ore, defined by the short-term mine planning module. This way, the management can plan the short-term mining operations (the weekly sequence of exploration blocks and the internal planning) in order to fulfill given required conditions, based on a shipment schedule and on a purchaser's formula. In this paper, after a short description of the short-term mining planning module and of the simulation package named SIMUL, a synthesis of the main model development steps and the results of some simulation runs are presented and discussed.